Interactive Learning Through Digital Media: Enchancing Elementary Math Instruction - Laurensi br Kaban; Maharani Puspa Sari; Matias Yoki; Mona Sihombing; Widya Pratiwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to increase the effectiveness of using interactive digital learning media in increasing students' understanding of mathematical concepts and learning motivation at the basic level. The research method used is a literature study by collecting and analyzing six selected articles that are relevant to the use of digital media in mathematics learning. The research results show that the use of interactive digital learning media increases students' understanding of mathematical concepts and learning motivation. Online applications such as Wordwall and digital image simulations such as MyWebAR are effective in teaching spatial shapes. Tools like Google Site and Google Classroom support bold learning. Digital media reduces misconceptions and increases interest in learning. There are various free websites available to choose suitable learning media. It is important for teachers to choose the right media for students.